Human Resource Development Climate. Culture and Mechanisms: The Case of United Bank Share Company - Teshome, Samson Worku; Ayalew, Lulit; Yifiru, Techane; W/Giorgis, Yebegasget; Beteselassie, Yishake; Bekele, Zelalem; Mekonnen, Worku (International Journal of Education, Management, and Technology, 2025)
This study aimed to assess the state of Human Resource Development (HRD) Climate, HRD Culture, and HRD Mechanisms at United Bank S.C., using a quantitative research design. A descriptive survey method was employed to explore three primary research questions: (1) Is the overall HRD climate at United Bank S.C. conducive? (2) To what extent does a supportive HRD culture exist within the organization? and (3) To what extent are HRD mechanisms implemented effectively at United Bank S.C.? A random sample of 60 employees was selected from the total population of 194 managerial and non-managerial staff. Data were collected using a standardized questionnaire comprising 38 items categorized under General HRD Climate, HRD Culture, and HRD Mechanisms. The responses were analyzed using the Statistical Package for the Social Sciences (SPSS). The findings revealed that the overall HRD climate in the organization is below average. Among the three components examined, HRD Culture was found to be more prominent than HRD Climate and HRD Mechanisms. Additionally, the study suggests that the organization places more emphasis on other resources than on the development of its human capital. The results highlight the need for United Bank S.C. to undertake strategic interventions aimed at strengthening its HRD climate by fostering a more robust culture of development and implementing comprehensive HRD mechanisms. Such measures are essential for enhancing organizational effectiveness and ensuring sustainable human capital growth.